2015
DOI: 10.1039/c4ay03080j
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of bisphenol A in food packaging based on graphene quantum dots and peroxidase

Abstract: A novel sensing strategy for bisphenol A was designed based on graphene quantum dots and peroxidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Fourier transform infrared (FTIR) spectra in Figure 3c indicated absorption of stretching vibration O–H, C–H, and C–OH groups [35]. To determine the size distribution of CDs dynamic light scattering (DLS) was employed [37, 38, 39, 40]. The result showed that CDs were under 5 nm in diameter (Figure 3d), in agreement with previous reports that showed the size distribution of carbon dots was under 10nm [41, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectra in Figure 3c indicated absorption of stretching vibration O–H, C–H, and C–OH groups [35]. To determine the size distribution of CDs dynamic light scattering (DLS) was employed [37, 38, 39, 40]. The result showed that CDs were under 5 nm in diameter (Figure 3d), in agreement with previous reports that showed the size distribution of carbon dots was under 10nm [41, 42].…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Owing to these properties, GQDs have immense potential applications in photovoltaic devices, 7 bioimaging instruments, 8 sensors and biosensors, 9,10 etc. Until now, GQDs have been used as a uorescent probe for the detection of a broad range of analytes such as metal ions, [11][12][13][14][15] organic matter, 16,17 proteins, 18 and other biomolecules. 19,20 Vanillin (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ruiling Sun et al found GQDs had the potential to be applied for analysing the contents of phenol in industrial water using the resonance light scattering method [21]. In food packaging, a detection method based on GQDs has been reported as an efficient approach for the analysis of bisphenol A [22]. Furthermore, GQDs coated with molecularly imprinted polymer have also been reported for the determination of 4-nitrophenol in water samples [23].…”
Section: Introductionmentioning
confidence: 99%